2017
DOI: 10.1164/rccm.201604-0871oc
|View full text |Cite
|
Sign up to set email alerts
|

Age and Small Airway Imaging Abnormalities in Subjects with and without Airflow Obstruction in SPIROMICS

Abstract: Rationale: Aging is associated with reduced FEV 1 to FVC ratio (FEV 1 /FVC), hyperinflation, and alveolar enlargement, but little is known about how age affects small airways. Objectives: To determine if chest computed tomography (CT)assessed functional small airway would increase with age, even among asymptomatic individuals. Methods: We used parametric response mapping analysis of paired inspiratory/expiratory CTs to identify functional small airway abnormality (PRM FSA) and emphysema (PRM EMPH) in the SPIRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 40 publications
3
56
0
Order By: Relevance
“…Half the subjects had an abnormal MDNW or IOS measurement, and in one quarter there was an overlap in abnormal IOS and MBNW variables. The results of the study and those from previous studies using physiological tests and CT imaging biomarkers demonstrate that small airway dysfunction is commonly found in this group of current and former smokers. Interestingly, smokers without spirometric COPD following smoking cessation show sustained improvements of conductive airway dysfunction (S cond ), but not in acinar airway function (S acin ) suggesting that some abnormalities of small airway disease are reversible, possibly due to reduced inflammation or hypersecretion …”
supporting
confidence: 61%
See 2 more Smart Citations
“…Half the subjects had an abnormal MDNW or IOS measurement, and in one quarter there was an overlap in abnormal IOS and MBNW variables. The results of the study and those from previous studies using physiological tests and CT imaging biomarkers demonstrate that small airway dysfunction is commonly found in this group of current and former smokers. Interestingly, smokers without spirometric COPD following smoking cessation show sustained improvements of conductive airway dysfunction (S cond ), but not in acinar airway function (S acin ) suggesting that some abnormalities of small airway disease are reversible, possibly due to reduced inflammation or hypersecretion …”
supporting
confidence: 61%
“…The function of peripheral airways is abnormal in some smokers without COPD assessed by physiological techniques, such as multiple breath nitrogen washout (MBNW) and impulse oscillometry (IOS) . Analysis of expiratory and inspiratory computed tomography (CT) images detects increased nonemphysematous air trapping, a surrogate for functional small airways disease, in ever‐smokers with normal spirometry . However, little is known about whether small airway dysfunction assessed by physiological tests, such as MBNW or IOS are worse in symptomatic smokers without COPD compared to asymptomatic smokers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First, our healthy reference group was not age matched to the relatively older IPF cohort. It is known that aging affects ventilation, and can reasonably be expected to similarly impair gas transfer. Therefore, future studies must also characterize gas transfer in older healthy subjects to better discriminate true disease from normal aging.…”
Section: Discussionmentioning
confidence: 99%
“…PRM-fSAD was also significantly associated with increasing age, especially in subjects without evident airflow obstruction and past smoking history. 82 Hoff and colleagues recently computed spatial relationship and local distributions of PRM-fSAD regions in COPD subjects. 78 These authors showed that the surface area of PRM-fSAD is an independent predictor of clinical outcomes in COPD.…”
Section: Applications In Copdmentioning
confidence: 99%